TEACHERS' PERCEPTION OF THE MERDEKA CURRICULUM IMPLEMENTATION IN ENGLISH VOCABULARY TEACHING AT RURAL ELEMENTARY SCHOOLS - Meiga Ratih Tirtanawati; Chyntia Heru Woro Prastiwi; Ariska dwi fatmasari (Universitas Aisyah Pringsewu, 2024)
The Merdeka Curriculum is a new policy in the Indonesian education sector that aims to give teachers and schools the freedom to design learning that suits students' needs and abilities. This research aims to determine teachers' perceptions of the implementation of the Merdeka Curriculum in English vocabulary lessons in rural elementary schools. The research method used is descriptive qualitative research. Data was collected through in-depth interviews with 3 class teachers in each elementary school in a rural area that had implemented the independent curriculum. The results of the research show that teachers have a positive perception of the implementation of the Merdeka Curriculum in English vocabulary lessons in rural elementary schools. Teachers feel that the Merdeka Curriculum gives them the freedom to design learning that is more creative and innovative, and better suited to students' needs and abilities. The findings of this research show that the Merdeka Curriculum has the potential to improve the quality of English language learning in elementary schools. However, further support is needed from the government and schools to assist teachers in implementing the Independent Curriculum effectively